PENGARUH PROFITABILITAS DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PT INDOFOOD CBP SUKSES MAKMUR Tbk PERIODE 2014-2023 - Dwi Utami, Rina; Rahman, Fakung (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of the variables Net Profit Margin (NPM) and Debt to Equitu Ratio (DER) on Price to Book Value (PBV) at PT Indofood CBP Sukses Makmur Tbk for the period 2014-2023. The research method used is causal associative with a quantitative approach. The data analysis used includes: Descriptive Statistical Test, Classical Assumption Test, Multiple Linear Regression Test, Hypothesis Test, and Determination Coefficient Test (R2) with the help of SPSS version 26. The results of this study indicate that the Net Profit Margin tcount is 1.343 < t table 2.306 with a significance value of (0.221> 0.05), meaning that Net Profit Margin has no significant effect on Price to Book Value. For the Debt to Equity Ratio variable tcount, the results obtained (4.759)> t table 2.306 with a significance value of (0.002 <0.05) means that the Debt to Equity Ratio has a negative and significant effect on Price to Book Value. Meanwhile, from the results of the F test (simultaneously), the significance value is obtained (0.006 <0.05) and the Fcount value is 11.500> Ftable 4.47, which means that the NPM and DER variables have a significant effect on PBV. As well as from the results of the Coefficient of Determination Test (R2), the R square value obtained a result of 0.767 which means that the effect of Net Profit Margin and Debt to Equity Ratio on Price to Book Value in this study is 76.70% while the remaining 23.30% is influenced by other variables not examined in this study.